Scale for Assessment of Nurse Manager Skills: A Scale Development Study - Gülcan Çiftçioğlu Yalçın; Emine Türkmen; Ülkü Baykal (Association of Nurse Managers, 2023)
Background: In hospitals, nurse managers have very important roles, duties and responsibilities in terms of achieving positive patient outcomes and organizational goals. In order for nurse managers to fully fulfill these roles, duties and responsibilities, they must have the necessary managerial skills. There are no valid and reliable tools to assess the skills of nurse managers. Objective: The aim of this study was to develop a tool (scale) to measure the evaluation of managerial nursing skills by subordinates. Method: This methodologically designed study was conducted with 698 nurses working in various hospitals in Turkey between February and June 2022 by online survey method. A draft scale form developed by the researchers by reviewing the relevant literature was used as a data collection tool. In the study, 10 expert opinions were taken for the content and face validity of the scale, and EFA and CFA were applied for the construct validity of the scale. For reliability, item analysis, Cronbach's alpha, 27% lower and upper quartile score correlation, halving method and test-retest analysis were used. Results: In the draft scale consisting of 66 items, the content validity index of 65 items, except for one item, was found to be between 0.80-1.00. In the exploratory factor analysis (EFA) conducted to examine construct validity, it was determined that the scale consisting of three sub-dimensions and 34 items explained 72.22% of the total variance. The Cronbach's alpha coefficient of the total scale was 0.99 and the test-retest correlation coefficient was 0.78. Conclusion: The scale consisting of 34 items and three sub-dimensions met the validity and reliability criteria. It would be useful to repeat the construct validity studies in future studies and discuss the results by using it in practice.